La Era Digital en la Química Farmacéutica: Transformando el Diseño de Medicamentos con Métodos Computacionales - Valdiviezo, Jesus (Pontificia Universidad Católica del Perú, 2023)
Drug design has significantly benefited from advancements in computational chemistry and neural networks. In this article, we explore the pivotal role played by computational chemistry techniques such as Density Functional Theory (DFT), Molecular Docking, and Molecular Dynamics (MD) in understanding and optimizing atomic and molecular-level interactions. Furthermore, we examine how the integration of neural networks has enhanced precision and efficiency in drug design. We present specific examples of research projects showcasing the synergy between these methods and highlighting substantial advances in the quest for effective medical solutions. Additionally, we discuss challenges and key considerations for continuing to progress in this multidisciplinary field.

El diseño de medicamentos se ha beneficiado significativamente de los avances en la química computacional y las redes neuronales. En este artículo, exploramos el papel fundamental que desempeñan técnicas de la química computacional como la Teoría del Funcional de la Densidad (DFT), el Docking Molecular y la Dinámica Molecular (MD) en la comprensión y optimización de interacciones a nivel atómico y molecular. Además, examinamos cómo la integración de redes neuronales ha impulsado la precisión y eficiencia en el diseño de fármacos. Presentamos ejemplos concretos de proyectos de investigación que demuestran la sinergia entre estos métodos y destacan avances significativos en la búsqueda de soluciones médicas efectivas. Asimismo, discutimos los desafíos y consideraciones clave para seguir avanzando en este campo multidisciplinario.
The Digital Era in Pharmaceutical Chemistry: Transforming Drug Design with Computational Methods
Keywords: Drug design; Computational chemistry; Artificial intelligence; Pharmacology; Diseño de medicamentos; Quimica computacional; Inteligencia artificial; Farmacología; https://purl.org/pe-repo/ocde/ford#1.04.00